Pengaruh Kualitas Pelayanan, Lokasi, Harga Dan Promosi Terhadap Pembelian Ulang Ayam Geprek Kak Rose (Studi Kasus Mahasiswa FEB unisma Angkatan 2018) - Mohammad Halimi; Agus Widarko; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of service quality, location, price and promotion on the return of Kak Rose's Geprek Chicken (Case Study of FEB Unisma Students Batch 2018). The variables used in this study are. Repurchase variable (dependent variable), while the independent variables are service quality, location, price and promotion.The results of this study partially conclude that the variables of service quality, location, price and promotion have a significant influence on repurchase and simultaneously conclude that there is a significant influence between service quality, location, price and promotion variables on repeat purchases.Keywords: Service Quality, Location, Price, Promotion, Repeat Purchase